UNREVALING SHARIA COMPLIANCE - Fardinant Adhitama; Achmad Soediro; Muhammad Farhan; Media Kusumawardani (AKUNTABILITAS, 2022)
This study is aimed at obtaining an in-depth explanation and understanding of the phenomenon of sharia compliance in an Islamic financial institution, Baitul Maal wat Tamwil (BMT) from the point of view of the members of BMT under LKSI group. The Rational Choice Theory and Bounded Rationality Theory are the two theories that used as an interpretation anchor and applied for analyzing the data. Sharia compliance of BMT members of the LKSI is reflected in every contract given to BMT clients/customers supported by regular training on the understanding of Islamic compliance on an ongoing basis. The activities are carried out with in considerations of two things, namely sharia and business science. Rational thinking based on the adherence to the religious values is an important basis in the formation of BMTs.